2015
DOI: 10.1007/s10067-015-2964-4
|View full text |Cite
|
Sign up to set email alerts
|

Is articular pain in rheumatoid arthritis correlated with ultrasound power Doppler findings?

Abstract: Intra-articular PD was not correlated with pain symptom in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…We found a clear sign of joint synovitis (synovial hypertrophy with or without PDS) in 40% of cases, more frequently in cases with a longer dactylitis duration and without pain. It is not surprising that patients with US-detected synovitis had no pain as other studies have already reported a disparity between clinical and US findings for synovitis in other rheumatic diseases [36][37][38]. In particular, pain was not correlated with GS synovitis and intra-articular PD in patients with rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 87%
“…We found a clear sign of joint synovitis (synovial hypertrophy with or without PDS) in 40% of cases, more frequently in cases with a longer dactylitis duration and without pain. It is not surprising that patients with US-detected synovitis had no pain as other studies have already reported a disparity between clinical and US findings for synovitis in other rheumatic diseases [36][37][38]. In particular, pain was not correlated with GS synovitis and intra-articular PD in patients with rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 87%
“…(110) We did not explore the value of being in ultrasound remission on other important patient related outcomes, such as pain, but previous studies indicate that the level of joint pain on a VAS scale do not correlate with ultrasound inflammation at one time point. (206,207)…”
Section: Association Between Subclinical Remission and Future Good Oumentioning
confidence: 99%
“…All these data suggest that local symptoms in active dactylitis are linked with extracapsular lesions, particularly flexor tenosynovitis and STOe, highlighting the central role of extra-articular structures in the genesis of digit pain. The sonographic evidence of joint synovitis does not seem to correlate with pain in the digit; this is not surprising since other rheumatic diseases demonstrate this same quality (Figure 2) [60][61][62].…”
Section: Correlation Between Imaging and Clinical Parametersmentioning
confidence: 96%